Ministry Of Finance Decree No. 55 of the Year 2021 on Collecting a Tax on the Returns of Treasury Bills = وزارة المالية قرار رقم 55 لسنة 2021 بشأن تحصيل الضريبة على عوائد أذون الخزانة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic